SOME APPROACHES TO THE REPRESENTATION OF REALITY FOR SOLVING PROBLEMS OF SPECIALISTS’ EDUCATION IN MODERN EDUCATIONAL ENVIRONMENT - Svetlana V. Zenkina; Vasilij M. Trembach (Открытое образование (Москва))
Article represents the features of modern educational environment for training specialists in the fi eld of aerospace robotics. Training requirements of modern specialists are pointed. Approaches to the description of the subject areas of onboard intelligent systems are demonstrated. Implementation variations of these approaches are shown in the architecture of an intelligent system and in the demo example of planning system.